The role of inflammation in pathogenesis and treatment of colorectal cancer - T. N. Garmanova; M. I. Bredikhin; I. A. Tulina; P. V. Tsarkov (Исследования и практика в медицине)
One of the factors affecting the effectiveness of treatment and determining the prognosis of a patient with colorectal cancer may be inflammatory status both before and after surgical treatment. The review is devoted to the description of possible mechanisms of relationa between patient's inflammatory status and oncogenesis. Particular attention is paid to the ability of tumor cells to modify the immune cells from the antioncogenic to prooncogenic status. The paper makes an attempt to present a unified concept of the impact of postoperative complications on tumor recurrence in the light of the inflammatory response to surgical intervention.